PERAN SEKTOR PERIKANAN TANGKAP DALAM MENDUKUNG KETAHANAN PANGAN PERIKANAN DI PROVINSI BANTEN - Adi Susanto; Asep Hamzah; Ririn Irnawati; Hery Sutrawan Nurdin; Fahresa Nugraheni Supadminingsih (Pusat Unggulan Iptek Ketahanan Pangan Universitas Sultan Ageng Tirtayasa, 2020)
Food availability is the first step to ensure the food access and the food utilization, to realize the food security in Banten Province. One sector that can play a role in supplying animal food is the capture fisheries sector. The capture fisheries sector contributes around 50% of the fish production in Banten Province. However, the level of fish consumption of Banten societies is relatively lower compared to eastern Indonesia region. This paper outlines a comparative descriptive analysis of the opportunities and roles of the capture fisheries sector in supporting the realization of food security in Banten Province.